2022
DOI: 10.3390/jcm11154494
|View full text |Cite
|
Sign up to set email alerts
|

The Immunohistochemical Assessment of Neoangiogenesis Factors in Squamous Cell Carcinomas and Their Precursors in the Skin

Abstract: Cutaneous squamous cell carcinoma (cSCC) is a common skin cancer. Well-limited forms can be easily treated with excision, but locally advanced cancers can, unfortunately, progress to metastasis. However, it is difficult to establish the prognosis for cutaneous squamous cell carcinoma and its potential to metastasize. Therefore, this study aimed to evaluate neoangiogenesis in cSCC, as it plays a major role in the dissemination of neoplasia. A literature review was performed on selected neoangiogenic factors (VE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…A recent review focused on the investigation of the factors involved in angiogenesis in cSCC and its precursors. Many of the studies indicated an increased expression of VEGF, especially in the advanced stages of the tumor [36]. Previous studies showed that VEGF expression correlated with the degree of tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review focused on the investigation of the factors involved in angiogenesis in cSCC and its precursors. Many of the studies indicated an increased expression of VEGF, especially in the advanced stages of the tumor [36]. Previous studies showed that VEGF expression correlated with the degree of tumor differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…To confirm whether BHGZD and the two-BACs-combination of MG and GA alleviated RA through inhibiting the revascularization process, the expression of CD31 and VEGFA proteins, both of which act as indicators for active intra-synovial revascularization [ 27 ], were detected. Our data showed that both the administration of BHGZD and the two-BACs-combination of MG and GA dramatically decreased the positive expression of CD31 and VEGFA proteins in the synovial tissues of knee joints in AIA-M rats.…”
Section: Discussionmentioning
confidence: 99%
“…Neovascularisation plays a critical role in tumor development and progression. Studies have previously demonstrated a significant increase in the microvascular area corresponding with the transition from AK to cutaneous SCC [34].…”
Section: Introductionmentioning
confidence: 97%